Antimicrobial effect of bothropstoxin-i in broilers - Silveira, Ana Carolina Portella; Gimenes, Sarah Natalie Cirilo; Barbaresco, Luiz Fernando; Carvalho, Camila Perdoncini; Bueno, João Paulo Rodrigues; Guimarães, Ednaldo Carvalho; Freitas, Paulo Fernando Alves de; Nascimento, Mara Regina Bueno de Mattos; Antunes, Robson Carlos; Ávila, Veridiana de Melo Rodrigues (Semina: Ciências Agrárias, 2021)
Bacterial resistance is a sanitary issue explained by indiscriminate use of nonprescription drugs, and antimicrobial use in food production for growth promotion. Bothropstoxin-I (BthTx-I) is a phospholipase A2 (PLA2) from Bothrops jararacussu venom, which has a known antimicrobial effect. The goal of this study was the unprecedented evaluation of in vivo antimicrobial activity of BthTx-I in broilers. Microbiological, biochemical, and histological parameters were determined using 84 21-day old broilers that were kept in cages with four birds each at a density of 625 cm2/broiler. The experiment was randomized by three treatments with seven repetitions of four broilers each that lasted seven days. The treatments were: 1) bacitracin zinc diet; 2) PLA2-BthTx-I; 3) without additives. The data obtained from the studied variables was subjected to analysis of variance and an F-test at the 5% significance level. Averages of each variable in each treatment were compared by Tukey's test. Broiler bacterial cloacal counts showed that BthTx-I decreased the microbial population without reducing body weight, intestinal morphology, or liver or kidney histopathological damage. The toxin showed in vivo activity, being an alternative for better performance in the production of broiler chickens, because it acted by decreasing the microbial load of potentially pathogenic bacteria in the intestinal microbiota of the birds and did not cause muscle, liver or kidney damage at the assessed dosage.